Public Sector Nurses' Experiences of Stress and Coping During the Covid-19 Pandemic: A Qualitative Study in the Western Cape, South Africa - Janse Van Vuuren, Marnus (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.